Substructures in Compact Disks of the Taurus Star-forming Region - Shangjia Zhang; Matt Kalscheur; Feng Long; Ke Zhang; Deryl E. Long; Edwin A. Bergin; Zhaohuan Zhu; Leon Trapman (The Astrophysical Journal, 2023)
Observations of substructure in protoplanetary disks have largely been limited to the brightest and largest disks, excluding the abundant population of compact disks, which are likely sites of planet formation. Here, we reanalyze ∼0.″1, 1.33 mm Atacama Large Millimeter/submillimeter Array (ALMA) continuum observations of 12 compact protoplanetary disks in the Taurus star-forming region. By fitting visibilities directly, we identify substructures in six of the 12 compact disks. We then compare the substructures identified in the full Taurus sample of 24 disks in single-star systems and the ALMA DSHARP survey, differentiating between compact ( R _eff,90% < 50 au) and extended ( R _eff,90% ≥50 au) disk sources. We find that substructures are detected at nearly all radii in both small and large disks. Tentatively, we find fewer wide gaps in intermediate-sized disks with R _eff,90% between 30 and 90 au. We perform a series of planet–disk interaction simulations to constrain the sensitivity of our visibility-fitting approach. Under the assumption of planet–disk interaction, we use the gap widths and common disk parameters to calculate potential planet masses within the Taurus sample. We find that the young planet occurrence rate peaks near Neptune masses, similar to the DSHARP sample. For 0.01 M _J / M _⊙ ≲ M _p / M _* ≲0.1 M _J / M _⊙ , the rate is 17.4% ± 8.3%; for 0.1 M _J / M _⊙ ≲ M _p / M _* ≲1 M _J / M _⊙ , it is 27.8% ± 8.3%. Both of them are consistent with microlensing surveys. For gas giants more massive than 5 M _J , the occurrence rate is 4.2% ± 4.2%, consistent with direct imaging surveys.